Superhydrophobicity, UV protection and oil/water separation properties of fly ash/Trimethoxy(octadecyl)silane coated cotton fabrics - Khan, Muhammad Zaman; Baheti, Vijay; Militky, Jiri; Ali, Azam; Vikova, Martina (Carbohydrate polymers, 2018)
The presented study proposed simple and low-cost approach for improvement in UV protection and superhydrophobic properties of cotton fabrics by coating of mechanically activated fly ash particles. The maximum UV blocking was observed for 3 wt% fly ash, where UV transmittance decreased from 14.19% of untreated fabric to 0.11% of coated fabric. After subsequent treatment of Trimethoxy(octadecyl)silane (OTMS) on fly ash coated fabrics, the water contact angle was increased to 143°, 147° and 153° for fly ash concentration of 1, 2 and 3 wt% respectively. From Cassie-Baxter theories, the unwetted fraction of air pockets were estimated to be 43%, 55% and 67% respectively for 1, 2 and 3 wt% of fly ash particles. Furthermore, the coated fabrics showed great potentials for separation of floating oil layer, underwater oil droplet or oil/water mixture. The separation efficiency of 98%, 96%, 97% and 95% was obtained for selected model oils toluene, n-hexane, chloroform and petro ether, respectively.
Keywords: Fly ash particles; Superhydrophobicity; Oil water separation; Cotton fabric; UV protection